(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research aimed to develop a module of environmental pollution based on local wisdom in Gunungkidul to improve the environmental care attitude of junior high school students. This research was a R&D (Research and Development). The development of this module adapted the steps of R&D research according to Sugiyono (2016), which was namely potential and problems, data collection, product design, design validation, design revision, product testing, product revision, usage trials, mass production. This first year research only covered potential problems, data collection, product design, design validation, and design revision. This module was created by placing indicators of environmental care attitude on each subject. Indicators of environmental care attitude include having awareness and gratitude for the culture; they had that must be maintained and preserved to protect the environment from pollution; they had curiosity, critical, and care about the environment in identifying the impact of environmental pollution; they had curiosity, critical, and care for the environment in identifying the impact of environmental pollution, and they must using our nature wisely and maintaining the balance of the ecosystem in the surrounding environment. The students’ environmental care attitude would also develop by placing Gunungkidul’s local wisdom in each module subject. The module got a very decent validation value in terms of material, media, and language.